Potensi nanopartikel chitosan berbasis flavonoid fisetin dari buah stroberi (Fragaria x ananassa): modalitas terapi dalam penatalaksanaan TNBC - Felicia Puspita Sari; Kenny Satrio; I Gede Gita Sastrawan; I Gusti Ngurah Bagus Rai Mulya Hartawan (Majalah Kedokteran Andalas, 2021)
Breast cancer is ranked number one in the world as a cancer with the highest new cases reaching 1.7 million people (43.4%). Triple-Negative Breast Cancer (TNBC) has a worse prognosis than non-TNBC because of low 5-year survival rates and high recurrence rates. TNBC was also rated as more aggressive and invasive with high levels of nuclear mitotics. Currently, the use of natural food substances derived from fruits, vegetables, and spices is getting more attention because of its role as chemopreventive and chemotherapeutic agents, one of which is flavonoids. Fisetin (3,3',4',7-tetrahydroxyflavone) is a flavonol bioactive molecule found in fruits and vegetables such as apples and persimmons with the highest concentration found in strawberries (Fragaria x ananassa). One of the technologies being developed in the oncology field is nanoparticles. Nanoparticles are useful for delivering and releasing drugs to the target organs, as well as increasing the bioavailability of drugs so that drugs can work for a longer time. The combination of the flavonoid fisetin encapsulated with chitosan nanoparticles has the potential to become one of the therapeutic modalities in the management of TNBC.